Facts and Photographs: Visualizing the Invisible with Spirit and Thought Photography - Margarida Medeiros (communication +1, 2015)
Photography has been related to a positivist aim since its beginning and its genealogy is generally drawn from the realism of the camera obscura. But when it comes to the sort of photographs usually called “spirit photography” and “fluid and thought photography”, classic theorists like Barthes, Rosalind Krauss and Tom Gunning tend to relate this practice with the magic and the ‘uncanny’ reception that occurred at its very beginnings. In this paper I will point out that the main question is to question the possibility of a “spiritualist document”, and, in this sense, we will connect this issue to the enlargement of the very notion of scientific “fact” as was being worked out by philosophers like William James and Frederick Myers inside and outside the spiritualist movement. We will try to underline the intense relationship between this kind of documents of the supernatural and the changes we can observe that were claiming for an enlargement of philosophical thought that could accept phenomena which were challenging rational argument. Note: Download statistics restarted from zero effective January 1, 2024. Please follow this link to see cumulative download statistics from our previous publishing platform: CPO Download Statistics 2012 - 2023
Keywords: spirit photography; positivism; fact; indexicality; objectivity